1999
DOI: 10.1046/j.1365-2222.1999.00477.x
|View full text |Cite
|
Sign up to set email alerts
|

Airway endothelin levels in asthma: influence of endobronchial hypertonic saline challenge

Abstract: These findings do not support the hypothesis that ET release within the airway lumen is involved in the bronchoconstrictor response induced by hypertonic saline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2000
2000
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…Though all of the five patients showed the highest concentrations 10 min after mannitol challenge, it has to be noted that we do not know how the tryptase levels behaved in those 25 subjects in whom the tryptase could not be assessed by our methods. Furthermore, previous investigators have usually failed to show a mast cell activation after a hyperosmolar challenge, especially when using tryptase as a mast cell indicator [10,30]. In conclusion, our study could not clarify whether hyperosmolarity can induce mast cell to release preformed mediators, like tryptase, in vivo .…”
Section: Discussioncontrasting
confidence: 64%
“…Though all of the five patients showed the highest concentrations 10 min after mannitol challenge, it has to be noted that we do not know how the tryptase levels behaved in those 25 subjects in whom the tryptase could not be assessed by our methods. Furthermore, previous investigators have usually failed to show a mast cell activation after a hyperosmolar challenge, especially when using tryptase as a mast cell indicator [10,30]. In conclusion, our study could not clarify whether hyperosmolarity can induce mast cell to release preformed mediators, like tryptase, in vivo .…”
Section: Discussioncontrasting
confidence: 64%
“…51 We have already demonstrated that injury to epithelial monolayers in vitro results in increased release of fibroproliferative and fibrogenic growth factors including fibroblast growth factor (FGF)-2, insulin-like growth factor-1 (IGF-1), platelet-derived growth factor (PDGF), endothelin (ET)-1 and latent and active TGF-β2. 35,52 We have also found that TGF-β, FGF-2 and ET-1 are increased in asthma, [53][54][55] with TGF-β and FGF-2 being encrypted in the extracellular matrix, as shown by their colocalization with the proteoglycans decorin and heparan sulfate, respectively. 56 To further establish the relationship between EGFR signaling in the repair and remodeling processes, we have used an EGFR-selective tyrosine kinase inhibitor that suppresses epithelial repair in vitro with a resultant increase in release of TGF-β2 by the damaged epithelial cells.…”
Section: Epithelial-mesenchymal Signalingmentioning
confidence: 98%
“…Elevated levels of endothelin have been detected in bronchoalveolar lavage¯uid from asthmatic subjects not taking glucocorticosteroid therapy (Redington et al 1995), consistent with an increase in the expression of immunoreactive endothelin in epithelium from biopsies taken from asthmatic subjects Redington et al 1997a). However, acute bronchoconstriction to allergen inhalation (Redington et al 1997c) or hypertonic saline (Makker et al 1999) does not appear to be associated with the release of endothelin-1. This is perhaps not surprising as this mediator is not stored and requires de-novo synthesis, which may occur several hours after acute challenge.…”
Section: Endothelinmentioning
confidence: 71%